Additive manufacturing with a flex activated mechanophore for nondestructive assessment of mechanochemical reactivity in complex object geometries. (12th September 2018) - Cao, Bo; Boechler, Nicholas; Boydston, Andrew J.
Abstract: We used digital light processing additive manufacturing (DLP-AM) to produce mechanochemically responsive test specimens from custom photoresin formulations, wherein designer, flex activated mechanophores enable quantitative assessment of the total mechanophore activation in the specimen. The manufactured object geometries included an octet truss unit cell, a gyroid lattice, and an "8D cubic lattice". The mechanophore activation in each test specimen was measured as a function of uniaxial compressive strain applied to the structure. Full shape recovery after compression was exhibited in all cases. These proof-of-concept results signify the potential to use flex activated mechanophore for nondestructive, quantitative volumetric assessment of mechanochemistry in test specimens with complex geometries. Additionally, the integration of DLP-AM with flex activated mechanophore build materials enabled the creation of customizable, three-dimensional mechanochemically responsive parts that exhibit small molecule release without undergoing irreversible deformation or fracture. Graphical abstract: Highlights: A resin containing flex activated mechanophores was developed and printed into elastomeric objects by DLP-AM. Mechanochemical reactivities of the printed objects bearing complex geometries were studied by compressing the samples. Mechanochemistry was used to report strain in 3Dprinted structures without inducing irreversible deformation.